PENERAPAN MODEL PENGAJARAN LANGSUNG BERBANTUAN MEDIA PRESENTASI PADA MATERI INDRA PENGLIHATAN DAN ALAT OPTIK DI SMK BARAMULI AIRMADIDI - Rende, Jeane Cornelda (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
This study aims to determine the improvement of learning outcomes of eleventh grade students at SMK Baramuli Airmadidi through the application of direct instruction model assisted by presentation media on the sense of sight and optical instruments. This research is a type of class action research. The subjects in this study amounted to 20 people. Data collection techniques in this study used test techniques with research instruments in the form of written tests. Data analysis techniques were quantitative and qualitative descriptive. The results showed that the application of direct instruction model assisted by presentation media was proven to improve the learning outcomes of eleventh grade students at SMK Baramuli Airmadidi on the sense of sight and optical instruments. This can be seen from the increase in student learning outcomes starting from the pre-cycle with an average value of 42 with a percentage of 0% completeness categorized as very low, then increasing in cycle I with an average value of 68 with a percentage of 45% completeness categorized as low, and increasing again in cycle II with an average value of 79 with a percentage of 100% completeness categorized as very high. This research is useful to add insight for teachers in terms of using learning strategies and learning media, so as to improve the quality of learning in the classroom.